Targeted delivery of liposomal senolytics to alleviate cellular senescence-induced bone loss - Rong Li; Yaohua Wei; Changhao Xiong; Jingwei Wang; Yixuan Lin; Ronghui Deng; Hao Qin; Yang Chen; Nan Li; Guyu Zheng; Yuanyuan Lv; Jian Shi; et al. (Fundamental Research)
The senescence of bone marrow-derived mesenchymal stem cells is involved in osteoporosis. The combination of dasatinib and quercetin has been explored to alleviate bone loss by efficiently reducing senescent cell populations. However, senolytic therapy by dasatinib and quercetin requires a precise ratio for better therapeutic effects, which is hard to achieve by oral administration. Meanwhile, the poor water solubility of these compounds limits their bioavailability, and their non-specific action could hamper effective penetration and targeting within relevant tissues. Herein, we developed alendronate-functionalized liposomes carrying dasatinib and quercetin (Aln-Lipo-DQ), focusing mainly on senescence-associated osteoporosis induced by chemotherapy or radiotherapy. Alendronate helps liposomes deliver dasatinib and quercetin to the femur and tibias, effectively removing senescent cells from bone tissue and increasing bone volume fraction from 5.05% to 11.95% in the chemotherapy-induced osteoporosis mouse model. We also found a 2.91-fold increase in bone volume fraction in Aln-Lipo-DQ treated groups compared to the control in radiotherapy models. This selectively targeting bone and reducing senescent cells holds great promise for cancer treatment-related and senescence-associated bone disorders.